Imaginaries of the Digital: Ambiguity, Power and the Question of Agency - Robin Mansell (Communiquer)
This paper considers both the empowering and the disempowering features of the digital environment in relation to the scope for individual and collective agency to shape the mediated environment. Digitally mediated life is disempowering for citizens much of the time as a result of power asymmetries framed by global capitalism. It is misleading, however, to suggest that digitally mediated communication is always exploitative. It is argued that the power dynamics within the prevailing digital governance regime need to be understood. Analysis of these dynamics often suggests that online participation coincides with a deterioration in the choices available to citizens, but contradictory dynamics nevertheless may yield opportunities for citizen empowerment and choice.